Intrinsic versus shape anisotropy in micro-structured magnetostrictive thin films for magnetic surface acoustic wave sensors. (8th November 2019) - Mishra, Harshad; Hehn, Michel; Lacour, Daniel; Elmazria, Omar; Tiercelin, Nicolas; Mjahed, Hamid; Dumesnil, Karine; Petit Watelot, Sebastien; Polewczyk, Vincent; Talbi, Abdelkrim; Bou Matar, Olivier; Hage-Ali, Sami
Abstract: This work aims at studying the interaction between surface acoustic waves (SAW) and micro-structured magnetostrictive layers under a magnetic field with a perspective to develop magnetic field sensors. The impact of the competition between the strong intrinsic magnetic anisotropy of the magnetic material and the shape anisotropy of the interdigitated transducer (IDT) fingers introduced by the micro-structuration is investigated. Therefore, the macroscopic and microscopic magnetic properties of the IDT and their influence on the magneto-acoustic response are studied. A SAW resonator with the IDTs made of the magnetostrictive thin film was elaborated and the magnetic surface acoustic wave (MSAW) response under a magnetic field was performed and discussed. Depending on the energy balance, the anisotropy gets modified and a correlation with the MSAW sensitivity to an externally applied magnetic field is made.